2020
DOI: 10.1063/1.5128756
|View full text |Cite
|
Sign up to set email alerts
|

Rapid discrimination of chemically distinctive surface terminations in 2D material based heterostructures by direct van der Waals identification

Abstract: We demonstrate that surfaces presenting heterogeneous and atomically flat domains can be directly and rapidly discriminated via robust intensive quantifiables by exploiting one-pass noninvasive methods in standard atomic force microscopy (AFM), single ∼2 min passes, or direct force reconstruction, i.e., ∼103 force profiles (∼10 min collection time), allowing data collection, interpretation, and presentation in under 20 min, including experimental AFM preparation and excluding only sample fabrication, in situ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Dean et al demonstrated, for the first time, the design of a heterostructure for enhanced nanoelectronic applications where graphene was successfully stacked with an hBN 2D material . Thereafter, many heterostructures have been developed and experimented on for their promise to fine-tune characteristics to suit specific applications in different areas. These alternately stacked layers exhibit greater chemical stability than either of their component layers separately, offering the opportunity to exploit the properties of their individual component materials …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dean et al demonstrated, for the first time, the design of a heterostructure for enhanced nanoelectronic applications where graphene was successfully stacked with an hBN 2D material . Thereafter, many heterostructures have been developed and experimented on for their promise to fine-tune characteristics to suit specific applications in different areas. These alternately stacked layers exhibit greater chemical stability than either of their component layers separately, offering the opportunity to exploit the properties of their individual component materials …”
Section: Introductionmentioning
confidence: 99%
“…In these heterostructure materials, van der Waals forces are believed to play a dominant role in gluing the different layers together, but the full picture remains elusive. , It is true that the van der Waals interactions exist at the interface of the sublayers, which can be seen in a number of studies carried out using contact angle measurements and atomic force microscopy, and this nonpolar interaction could be the dominating factor that stabilizes the heterostructures. ,, On the other hand, the phenomenon of partial charge transfer (polar interaction) among the heterostructure sublattices is also speculated to be an important factor behind the stability of the compounds. ,, Particularly, for superconductivity in heterostructures, interface charge transfer and electron–phonon coupling have also been suggested as crucial interactions among their component layers. , Therefore, to understand the atomic-scale phenomenon of charge transfer and/or van der Waals interactions, a comprehensive study of the crystal structure and sublayer alignment is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was impossible to reproduce the experimental results by employing forces of the type predicted in Figure a, but we could reproduce them when using profiles as in Figure b. We further note that the attractive part of the force is convex, as found in our initial experimental work by reconstructing the force, and that this has been consistently corroborated since then. The actual shape of the experimental curve was more thoroughly incvestigated and compared to the standard power laws predicted by models in ref .…”
Section: Discussionmentioning
confidence: 67%
“…We have thoroughly investigated the evolution of the tip−sample force as it varies in time as samples are exposed to the air environment for several years. 66,67 Much of our work is on graphite, 82 graphene, 41,86 calcite, 27,87,88 and Si substrates. 27 Our results have been interpreted and corroborated by exploiting attenuated total reflectance infrared spectroscopy (ATR IR), 86 Fourier-Transform IR (FTIR), 82,89 static (SCA) and dynamic (DCA), advancing and receding, 82 contact angle measurements, surface free energy, 41 and DFT calculations.…”
Section: P W Ementioning
confidence: 99%